"The Price of Disaster": The Charter School Authorization Process in Post-Katrina New Orleans. Issue 2 (March 2021) - Henry, Kevin Lawrence
Charter schools because of their entanglements with privatization remain one of the most publicly contested and controversial educational reform initiatives. Charter schools, in theory, are to balance autonomy and accountability in order to provide students with innovative learning environments and increased achievement on traditional academic measures. The governance of charter schools and the vision espoused in the charter application are central in determining the organization and operation of charter schools. As such, connected to charter schools are the actors that envision them and the processes and policies that enable them. Utilizing the case of post-Katrina New Orleans, I examine the charter authorization process, an understudied aspect of charter school policy. Understood as an objective, colorblind process in mainstream policy articulations, the authorization process regulates entry into educational markets. This paper applies a Critical Race Theory analysis to the authorization process. I argue the charter school authorization process is a foundational gatekeeping mechanism that structures charter markets. In so doing, the charter school authorization process is embedded within and constitutive of on-going processes of racial formation and racialized power solidification. Moreover, I argue mainstream policy articulations situate the charter school authorization process as an accountability mechanism that is neutral, benign, and objective; such articulations distort and distract from the racial antagonisms upon which neoliberal reform projects are built.